Consensus in preference-approvals: A weighted distance approach - García-Lapresta, J.L.; Pérez-Román, D.; Erdamar, B.; Sanver, M.R. (World Scientific Publishing Co. Pte Ltd, 2012)
Measuring consensus level for a set of preferences requires a proper distance defined on the considered domain. We focus on preference-approvals which are extensions of ordinal preferences by the approval information. For any given set of alternatives, a preference-approval is defined by a weak ordering of the alternative set, subsets of approved and disapproved alternatives and a consistency condition. We propose a method of using weighted distances for ordering and approval components. A consensus measure based on this distance is provided which is sensitive to the position of the disagreements on ordering and approval.
Belgian Nuclear Research Centre (SCK-CEN);Ghent University
10th International Fuzzy Logic and Intelligent Technologies inNuclear Science Conference, FLINS 2012 -- 26 August 2012 through 29 August 2012 -- Istanbul -- 102034
Keywords: Decision Making; Uncertainty Analysis; Consistency Conditions; Ordinal Preference; Weighted Distance; Weighted Distance Approach; Fuzzy Logic